2002
DOI: 10.1136/bmj.324.7350.1358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of routine zinc supplementation on pneumonia in children aged 6 months to 3 years: randomised controlled trial in an urban slum

Abstract: Objectives To evaluate the effect of daily zinc supplementation in children on the incidence of acute lower respiratory tract infections and pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
96
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 18 publications
6
96
1
6
Order By: Relevance
“…A study conducted in Ecuador showed that when children with malnourishment were supplemented with zinc for 60 days, they had a lesser incidence of respiratory infections with fever and cough. 25 Other large trials from India and Bangladesh also have confirmed a lesser incidence of ARI in children supplemented with zinc. 26 The association of Zn supplementation with the reduction in the average days of oral antibiotic usage required to treat ARIs was also studied in children with cystic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Ecuador showed that when children with malnourishment were supplemented with zinc for 60 days, they had a lesser incidence of respiratory infections with fever and cough. 25 Other large trials from India and Bangladesh also have confirmed a lesser incidence of ARI in children supplemented with zinc. 26 The association of Zn supplementation with the reduction in the average days of oral antibiotic usage required to treat ARIs was also studied in children with cystic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is a trace metal that is an important cofactor for numerous enzymes in the body and plays a key role in the immune response (22). Zinc deficiency has been implicated in the development of pneumonia in children of third world countries (23,24), and dietary zinc supplementation in these children decreases susceptibility to infection and improves overall health outcomes (25,26). Importantly, recent experimental studies have shown that alcohol-fed animals have lower zinc levels in the lung compared with controlfed animals, and dietary zinc supplementation can reverse the pulmonary immune dysfunction seen with chronic alcohol ingestion (21,27).…”
mentioning
confidence: 99%
“…Contrastada con la de nuestro estudio, la incidencia de infección respiratoria aguda también fue menor en los niños que consumieron algún tipo de zinc y se evidenció un riesgo menor de desarrollar dicha enfermedad (RR=0,45, IC 95% : 0,247 a 0,842, p=0,016). Además de los beneficios del zinc frente al resfriado común, varios ensayos clínicos han demostrado su utilidad en el manejo adjunto de la neumonía en niños menores de cinco años tal como lo describen Black (25), Brooks (26) y Bhandari (27).…”
Section: Discussionunclassified